Biosurfactant from Nile Papyrus endophyte with potential antibiofilm activity against global clones of Acinetobacter baumannii - Amer, Mai A.; Wasfi, Reham; Hamed, Samira M. (Frontiers in Cellular and Infection Microbiology, 2023)
Acinetobacter baumannii is a leading cause of biofilm-associated infections, particularly catheterrelated bloodstream infections (CRBSI) that are mostly recalcitrant to antimicrobial therapy. One approach to reducing the burden of CRBSIs is inhibiting biofilm formation on catheters. Owing to their prodigious microbial diversity, bacterial endophytes might be a valuable source for biosurfactants known for their great capacity to disperse microbial biofilms. With this in mind, our study aimed to screen bacterial endophytes from plants growing on the River Nile banks for producing powerful biosurfactants capable of reducing the ability of A. baumannii to form biofilms on central venous catheters (CVC). This was tested on multi-/extensively drug resistant (M/XDR) clinical isolates of A. baumannii that belong to high-risk global clones and A. baumannii ATCC 19606. The drop collapse and oil dispersion assays were employed in screening the cell-free supernatants (CFS) of all endophytes for biosurfactant activity. Of the 44 bacterial endophytes recovered from ten plants, the CFS of Bacillus amyloliquefaciens Cp24, isolated from Cyperus papyrus, showed the highest biosurfactant activity. The crude biosurfactant extract of Cp24 showed potent antibacterial activity with minimum inhibitory concentrations (MIC) ranging from 0.78 to 1.56 mg/ml. It also showed significant antibiofilm activity (p-value < 0.05). Sub-MICs of the extract could reduce biofilm formation by up to 89.59%, while up to 87.3% of the preformed biofilms were eradicated by the MIC. A significant reduction in biofilm formation on CVC impregnated with sub-MIC of the extract was demonstrated by CV assay and further confirmed by scanning electron microscopy. This was associated by three log10 reduction in adhered bacteria in the viable count assay. GC-MS analysis of the crude biosurfactant extract revealed the presence of several compounds (saturated, unsaturated and epoxy fatty acids, cyclopeptides and 3-Benzyl-hexahydro-pyrrolo [1, 2-a] pyrazine-1,4-dione) potentially implicated in the potent biosurfactant and antibiofilm activities. Here we report the isolation of a B. amyloliquefaciens endophyte from the plant C. papyrus that produces a biosurfactant with potent antibiofilm activity against MDR/XDR global clones of A. baumannii. The impregnation of CVCs with the biosurfactant was demonstrated to reduce biofilms and, hence, proposed as a potential strategy for reducing CRBSIs.